2013
DOI: 10.1155/2013/253210
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neurotransmitters in Protection against Amyloid-β Toxicity by KiSS-1 Overexpression in SH-SY5Y Neurons

Abstract: Recent studies have suggested that the kisspeptin (KP) and kissorphin (KSO) peptides have neuroprotective actions against the Alzheimer's amyloid-β (Aβ) peptide. Overexpression of the human KiSS-1 gene that codes for KP and KSO peptides in SH-SY5Y neurons has also been shown to inhibit Aβ neurotoxicity. The in vivo actions of KP include activation of neuroendocrine and neurotransmitter systems. The present study used antagonists of KP, neuropeptide FF (NPFF), opioids, oxytocin, estrogen, adrenergic, cholinergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…We also found that treatment of amyloid peptides such as Aβ and Aβ 25-35 , nearly halved cell viability. The extent of sensitivity to amyloid peptides was similar to that of previously published values (9,11,12,13,15,18). These evidence suggests that the use of DMEM (supplemented with 10%FBS and antibiotics) is the best culture medium for both PC12 and SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that treatment of amyloid peptides such as Aβ and Aβ 25-35 , nearly halved cell viability. The extent of sensitivity to amyloid peptides was similar to that of previously published values (9,11,12,13,15,18). These evidence suggests that the use of DMEM (supplemented with 10%FBS and antibiotics) is the best culture medium for both PC12 and SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 87%
“…As models of neurons, rat PC12 pheochromocytoma cells (6) and human SH-SY5Y neuroblastoma cells (7,8) have been used by many investigators to search for neuroprotective substances. However, the composition of the culture media they have used is quite different from researcher to researcher: RPMI1640 (differentiated PC12) (9, 10), RPMI (PC12) (11), DMEM (PC12) (12,13), DMEM (SH-SY5Y) (14), DMEM/Ham's F-12 (1:1) (SH-SY5Y) (15,16), MEM/F-12 (SY-SY5Y) (17) and DMEM/F-12 + non-essential amino acids (SH-SY5Y) (18), all supplemented with serum and antibiotics. It is not clear why the inclusion of F-12 and non-essential amino acids is necessary to culture SH-SY5Y cells.…”
mentioning
confidence: 99%
“…Furthermore, it has recently been reported that neuronal protection caused by blackberry polyphenols is produced by mechanisms other than modulating reactive oxygen species (ROS) levels [ 52 ]. It is possible that both oxidative and other mechanisms, such as: Autophagy [ 21 ]; heat shock protein (HSP)-70 [ 22 ]; JAK2/STAT5/Bcl-xL [ 24 ]; phosphor HSP-20 [ 28 ]; amyloid disaggregation [ 29 ]; and, the overexpression of the KiSS gene [ 30 ], may be involved in the induction of neurotoxicity (column D in Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no uniformity in the culture condition of PC12 and SH-SY5Y cells in previous investigations. The culture media used was: Dulbecco’s modified Eagle’s medium (DMEM); the minimum essential medium (MEM); RPMI1640; a mixture of DMEM and Ham′s F12 (1:1); and, non-essential amino acids (NEAA), which were supplemented with fetal bovine serum (FBS), alone or together with, horse serum (HS) (column A in Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Differentiated and undifferentiated cells (column B), inoculated at different cell densities, were exposed to considerably different concentrations of neurotoxic agents (column C) in uncoated, collagen, or poly-lysine-coated plates ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…GABRA6 [64], GABRA1 [65], GABRG2 [66], SLC4A10 [67], HCN1 [68], GABRA4 [69], KCNC2 [70], SCN2A [71], SYN2 [72], FGF12 [73], SCN8A [74], OLFM3 [75], PLCB1 [76], KCNQ5 [77], TUBB2A [78], SIK1 [79], ABCC2 [80], SLC6A12 [81] and COL6A2 [82] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [83], CXCL11 [84], EGR1 [85], CALB1 [86], BDNF (brain derived neurotrophic factor) [87], TERT (telomerase reverse transcriptase) [88], NEFL (neurofilament light) [89], SNAP25 [90], RPH3A [91], NRN1 [92], SYT1 [93], GRIN2B [94], AVP (arginine vasopressin) [95], VSNL1 [96], HTR2A [97], PAK3 [98], STXBP5L [99], HCRTR2 [100], SYP (synaptophysin) [101], SYT10 [102], PRKCE (protein kinase C epsilon) [103], NRG1 [104], KISS1 [105], NRXN3 [106], RAB3A [107], IGF1 [108], PLK2 [109], CBLN4 [110], CAP2 [111], SV2B [112], CAMK4 [113], INA (internexin neuronal intermediate filament protein alpha) [114], GAP43 [115], TTR (transthyretin) [116], CXCR2 [117], IL1R2 [118], CXCR4 [119], CCR2 [120], MYOCD (myocardin) [121], S100A12 [122], CXCR3 [123], PROK2 [124], CXCL8 [125], RGS1 [126], NOTCH3 [127], P2RX7 [128], NGFR (nerve growth factor receptor) [129], GDF15 [130], CR1 [131], ADORA2A [132], GPER1 [133], FCGR2B [134], MMP9 [135], CNN2 [136...…”
Section: Discussionmentioning
confidence: 99%